Leisure physical activity of people with and without chronic non-communicable diseases - Thainá Ferreira de Toledo Piza; Paula Parisi Hodniki; Sinval Avelino dos Santos; Maria Teresa da Costa Gonçalves Torquato; Adrielen Aparecida Silva Calixto; Rute Aparecida Casas Garcia; Carla Regina de Souza Teixeira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the leisure physical activity of people with and without chronic non-communicable diseases by the single health system of the city of Ribeirão Preto - São Paulo. Methods: observational cross-sectional study, data were collected by means of interviews in a sample for convenience and random of adults. Results: there were 719 people, where 70.1% had chronic non-communicable diseases, being 68.1% inactive. Physical inactivity presents a similar distribution between the groups with and without disease and a national average in leisure physical activity. Conclusions: these data are aimed at health services that do not encourage physical and auditory leisure activities, such as multiprofessional activities in the health area.